Arquitectura del paisaje. Intervención en el Cementerio El Ángel y Museo Cementerio Presbítero Maestro - Burga Canales, Bayron Henry (2023)
Cemeteries are spaces where citizens interact with the past. The memory, the senses and the emotions that are manifested within these environments have made the link with the cemeteries special and different from other buildings. Since its inception, cemeteries have been moved out of cities for health reasons. However, the lack of planning led to a disorderly growth of cities, urban cemeteries were encapsulated and isolated within it. These cemeteries are crowded, at present, and in most cases, they are unused. Despite this, many buildings of historical and artistic value are located inside, which accumulated throughout its evolution. The disorderly growth and the deficit of public space have prompted the search for new strategies to obtain space for recreation and green areas. One of the most successful is the recycling of unused equipment. This "recycling" of equipment and the new ways of thinking about death and burial have influenced the vision of cemeteries. This new current, of European origin, proposes cemeteries as public spaces for enjoyment due to their accessibility and large extensions of green areas and trees without losing their identity as historical infrastructure of the city. This type of cemeteries is being accepted internationally and is already present in some Latin American countries. In the national context, the urban cemeteries of the city of Lima (such as the Cementerio El Ángel and the Museo Cementerio Presbítero Maestro) have the potential to develop as new typologies of natural spaces through urban strategies around the landscape, edges and walking trails.